After the panic: Are financial crises demand or supply shocks: Evidence from international trade - Benguria, Felipe and Taylor, Alan M. (The American Economic Review: Insights)
Are financial crises a negative shock to aggregate demand or supply? This is a fundamental question for research and policy making. Arguments for stimulus usually presume demand-side shortfalls; arguments for tax cuts or structural reform look to the supply side. Resolving the question requires models with both mechanisms, and empirical tests to tell them apart. We develop a small open economy model, where a country is subject to deleveraging shocks that impose binding credit constraints on households and/or firms. These financial crisis events leave distinct statistical signatures in the time series record that divide sharply between each type of shock. Empirical analysis reveals a clear picture: after financial crises the dominant pattern is that imports contract, exports hold steady or even rise, and the real exchange rate depreciates. History shows financial crises are predominantly a negative shock to demand.- Reproduced
Keywords: Economic History: Transport, International and Domestic Trade, Energy, Technology